Achievement of maximal SARS-CoV-2 collective immunity among the Tajik population by March 2022 - A. Yu. Popova; V. S. Smirnov; S. A. Egorova; J. A. Abdullozoda; M. M. Ruziev; A. M. Milichkina; V. A. Ivanov; S. D. Vokhidov; E. S. Ramsay; M. M. Mullodzhanova; I. V. Drozd; B. T. Holova; et al. (Медицинская иммунология, 2023)
Despite all efforts of the world community, the COVID-19 pandemic remains one of the main epidemiological challenges of our time. Even with its widespread distribution, the infection may have certain local features due to social, geographic, and climatic factors. Objective: to study collective immunity to SARS-CoV-2 in the population of the Republic of Tajikistan.A cross-sectional, randomized study of herd immunity was carried out according to a program developed by Rospotrebnadzor and the St. Petersburg Pasteur Institute, taking into account WHO recommendations. The ethics committees of the corresponding entities approved the study: Tajik Ministry of Health and Social Protection; and the St. Petersburg Pasteur Institute (Russia). Based on questionnaire results, 4,022 people were selected, representing 0.15% (95% CI: 0.14-0.15) of the total population randomized by age and region. In subsequent laboratory analysis, 3682 people took part. The distribution and quantitative content of antibodies (Abs) to viral nucleocapsid (N Ag) and receptor binding domain (RBD Ag) were determined by ELISA. When questioned, a history of SARS-CoV-2 vaccination was indicated by 69.7% (95% CI: 68.2-71.2) of the volunteer cohort. Vector vaccines were most frequently used (50.6%; 95% CI: 48.7-52.5), with whole-virion inactivated preparations in second place (23.0%: 95% CI: 21.4-26.6) and mRNA vaccines in third place (21.0%; 95% CI:19.4-22.6).The cohort (n = 3682) featured 27.5% men and 72.5% women. The overall seroprevalence was 98.5% (95% CI: 97.7-99.2) in men and 99.4% (95% CI: 99.0-99.6) in women (differences statistically insignificant). Overall seroprevalence in the cohort was 99.2% (95% CI: 98.8-99.4) and ranged from 97.2 to 100% in certain subgroups. Asymptomatic seropositivity in the whole cohort was 98.4% (95% CI: 97.6-99.1). As a result of a mandatory vaccination program introduced in Tajikistan under a COVID-19 Emergency Project, the level of herd immunity among vaccinated individuals reached 99.5% (95% CI: 99.1-99.7), which is similar to the level reached in the cohort as a whole.The epidemic situation that developed in Tajikistan by mid-March 2022 was characterized by an almost absolute level of herd immunity, as evidenced by an absence of detected overt COVID-19 cases since the end of February (2022).